Sierra Leone : Sixth Review Under the Poverty Reduction and Growth Facility Arrangement, Requests for Waiver of Performance Criteria and Additional Interim Assistance Under the Enhanced Initiative for Heavily Indebted Poor Countries, Review of Financing Assurances, and Ex Post Assessment of Longer-Term Program Engagement. (IMF Staff Country Reports; Country Report ;, 2005)
This report reviews developments during 2004 in the context of the Sixth and Final Program Review Under Sierra Leone's Poverty Reduction and Growth Facility (PRGF) arrangement with the IMF. The authorities have implemented an economic reform program supported by a PRGF arrangement since 2001. The authorities also request a further extension of interim Heavily Indebted Poor Countries (HIPC) Initiative assistance to Sierra Leone because of the exceptional circumstances of the country's highly vulnerable external position and the need to help smooth out the profile of debt service payments to the IMF.